Bilateral adrenal histoplasmosis: endoscopic ultrasound – guided fine needle aspiration as a method of diagnosis and assessment - Jaafar, Khairul Azhar; Hwang Siok Gek, Jacqueline; Lim Kiat Hon, Tony; Tan , Ban Hock; Mesenas, Steven (Malaysian Medical Associations, 2011)
We report a case of a healthy 78 -year- old indonesian man who presented with chronic weight loss, poor appetite and lethargy. CT abdomen showed bilateral adrenal masses. Endoscopic ultrasound(EUS) – guided FNA was performed on the left adrenal gland. The histopathology report was Histoplasma Capsulatum. He recovered well with antifungal treatment without any complication. In this case, we found that the role of EUS – guided FNA was not only limited to diagnosis but also helped in the prognosis of the disease since the method was able to assess the general anatomy of the adrenal gland better than other imaging modalities due to its close proximity and direct visualization.